PENGEMBANGAN BUKU PANDUAN MENULIS TEKS EKSPLANASI KELAS VI SDN KARANGWULUH - Zulfikar, Muhammad; Rochmiyati, Siti (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2023)
This research aims to develop a guidebook for writing explanatory texts to improve the writing skills of class VI students at SDN Karangwuluh, Kulon Progo Regency. This research uses a research and development (R&D) approach based on Sugiyono's theory which has been adapted to research needs into seven implementation stages, namely: 1) data collection, 2) product design, 3) design validation, 4) design review, 5) product testing, 6) trial use, and 7) final product. The results of this research show that: (1) the guidebook was developed according to the student and teacher needs questionnaire; (2) valid guidebook based on validation from material experts and media experts. Obtained a percentage of 82% in the very appropriate category from material experts and a percentage of 83.5% in the very appropriate category from media experts; (3) the percentage of teacher responses after using the guidebook classically was 91.38% with very good criteria, the percentage of classical student responses was 88.82% with very good criteria; (4) the guidebook is effectively used in learning to write explanatory texts, the results of the t-test average difference analysis are 8.940 and the average increase (gain) is 0.71 with high criteria. The conclusion of this research is that the guidebook is suitable for use in learning activities.